2023
DOI: 10.1021/acsomega.3c02784
|View full text |Cite
|
Sign up to set email alerts
|

Deep and Transfer Learning Approaches for Automated Early Detection of Monkeypox (Mpox) Alongside Other Similar Skin Lesions and Their Classification

Madhumita Pal,
Ahmed Mahal,
Ranjan K. Mohapatra
et al.

Abstract: The world faces multiple public health emergencies simultaneously, such as . mpox, from being a neglected disease, has emerged as a global threat that has spread to more than 100 nonendemic countries, even as COVID-19 has been spreading for more than 3 years now. The general mpox symptoms are similar to chickenpox and measles, thus leading to a possible misdiagnosis. This study aimed at facilitating a rapid and high-brevity mpox diagnosis. Reportedly, mpox circulates among particular groups, such as sexually p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…This contributes significantly to the early and accurate detection of mpox skin lesions. 53 The majority of respondents in the present study showed high levels of confidence in the ability of the general public and the local health authorities to control human mpox, even though it would negatively impact the economy. This confidence could have stemmed from the firsthand experience during the COVID-19 pandemic, where the World Health Organization (WHO) and health authorities have gained significant empowerment over the last three years.…”
mentioning
confidence: 62%
“…This contributes significantly to the early and accurate detection of mpox skin lesions. 53 The majority of respondents in the present study showed high levels of confidence in the ability of the general public and the local health authorities to control human mpox, even though it would negatively impact the economy. This confidence could have stemmed from the firsthand experience during the COVID-19 pandemic, where the World Health Organization (WHO) and health authorities have gained significant empowerment over the last three years.…”
mentioning
confidence: 62%
“…Nave Bayes algorithm achieved 91% accuracy in sorting mpox from other skin lesions outperforming various CNNs and shallow classifiers including GoogLeNet, AlexNet, VGG‐16, SVM, RF and DT 82 . A very recent study demonstrated that Inception v3 is the best model with 97.48% precision, 95.67% recall, 96.56% F1‐score and 96.56% accuracy in detecting mpox virus 83 . With a unique augmentation approach, this model returned 100% training accuracy and 96.56% validation accuracy.…”
Section: Artificial Intelligence As a Befitting Toolmentioning
confidence: 99%
“…82 A very recent study demonstrated that Inception v3 is the best model with 97.48% precision, 95.67% recall, 96.56% F1-score and 96.56% accuracy in detecting mpox virus. 83 With a unique augmentation approach, this model returned 100% training accuracy and 96.56% validation accuracy. As per the study, Inception v3 is a potentially valuable tool for early, automatic and accurate diagnosis of mpox as also other skin lesion diseases such as smallpox, chickenpox, measles, etc.…”
Section: Artificial Intelligence As a Befitting Toolmentioning
confidence: 99%
“…For example, S. N. [1] developed a monkeypox skin lesion dataset (MSLD) and tested models like VGG16, ResNet50, and InceptionV3, finding out that at 82.96%, ResNet50 achieved the best accuracy. M. Pal et al (2023) [2] similarly evaluated CNNs on the multiclass classification of monkeypox vs chickenpox and measles, with InceptionV3 reaching 96.56% accuracy.…”
Section: Literature Surveymentioning
confidence: 99%